2019
DOI: 10.21203/rs.2.18506/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of the pharmacogenetics of ARMS2 A69S polymorphism and the response to advanced age-related macular degeneration

Abstract: Background Age-related macular degeneration (AMD) causes irreversible vision loss, and targeted anti-vascular endothelial growth factor (VEGF) therapy is now the most common and effective treatment. The aim of this meta-analysis is to discuss whether genetic polymorphism of ARMS2 A69S could confer susceptibility to advanced AMD with the response to anti-VEGF treatment.Methods We performed a meta-analysis of relevant published studies selected through electronic databases. A total of 21 preferred studies regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Diabetic self-management education was found to improve regular follow-up for diabetes care, including eye and vision care, in rural patients. 182 A systematic review 290 of the effectiveness of interventions to promote screening for DR showed that the following interventions were effective: increasing patient and provider awareness of DR, improving access to health care, implementing computerbased registration or reminder systems, fostering collaboration among local organizations that provide retinal screening, and developing a community-based health care system. A reminder was the most frequently used intervention to promote retinal screening, and it was more effective if sent to both physicians and patients.…”
Section: Improve Access To Eye Carementioning
confidence: 99%
“…Diabetic self-management education was found to improve regular follow-up for diabetes care, including eye and vision care, in rural patients. 182 A systematic review 290 of the effectiveness of interventions to promote screening for DR showed that the following interventions were effective: increasing patient and provider awareness of DR, improving access to health care, implementing computerbased registration or reminder systems, fostering collaboration among local organizations that provide retinal screening, and developing a community-based health care system. A reminder was the most frequently used intervention to promote retinal screening, and it was more effective if sent to both physicians and patients.…”
Section: Improve Access To Eye Carementioning
confidence: 99%